Organophosphorus compounds .118. Reactions of 1-chloro-1H-phosphirenes with nucleophiles - Göller, Andreas H.; Clark, Timothy; et al. (Chemische Berichte, 1997)
The halogen atoms in the 1-chloro-1H-phosphirenes, 5a-c, are easily substituted on reaction with organolithium and Grignard reagents, 14a-p, with formation of the corresponding O-, N-, C-, Si-, and Ge-substituted 1H-phosphirenes, 15a-t. Cl/H exchange reactions also occur on reaction with lithium metal hydrides (5a –> 17). Furthermore, substitution reactions are also realized with the alkali metal berates, 18a-g (–> 19a-g); the same is true for reactions with trimethylsilyl cyanide and azide (–> 22a-d). Some of the substitution products have been characterized in the form of their metal complexes, 16, 23, 24, and 25.
Keywords: phosphorus heterocycles; 1H-phosphirenes; nucleophilic substitution reactions at 1H-phosphirenes; metal-complexation of functionalized 1H-phosphirenes; carbonyl complexes